The effects of RNAi soybean lines on Dectes texanus larval development - Filbert, Sophie Ann (Kansas State University, 2023)
Dectes stem borer, Dectes texanus, is a coleopteran arthropod pest that infests sunflowers and soybeans. The larvae, the damaging life stage, feed downward through the stem to its base where they girdle the stem to create an overwintering site. It has been observed that Dectes stem borer causes significant soybean yield loss due to lodging, and few control methods are available. Contact insecticides will not kill stem burrowed larvae and multiple sprays are needed to negatively impact adult populations. Producers may employ cultural practices, such as early harvest before lodging can occur; however, cultural control is dependent upon uncontrollable factors, such as weather. RNAi was evaluated as a possible strategy for Dectes stem borer larval control. Previous in vitro experiments were conducted and demonstrated that dsRNA injection or dsRNA diet, using dsRNA that targets critical genes in Dectes, could inhibit development of Dectes larva. Our research continued this project to determine if host induced gene silencing (HIGS) could be an effective method to control Dectes stem borer. Three genes (Laccase 2, Chitin Synthase II, and CYP9E) in Dectes were targeted for these experiments. Through host-induced gene silencing, the RNAi lines were hypothesized to cause cuticle deformations in the adult beetle, lower chitin content in the midgut of the larvae, and cause delayed growth and mortality in the larvae, respectively. Those negative effects would in turn cause slowed or no tunneling in soybean stems. Transgenic events were created expressing these genes and were used for both greenhouse and field-based experiments. The field research trial was deployed at the Agronomy North Farm in Manhattan, Kansas where high Dectes pressure has been observed in previous years. The transgenic RNAi soybean lines, as well as a control non-transgenic line, were planted, and stem tunneling data was collected and analyzed to compare stem tunneling between each line and the non-transgenic control. The data suggests more research needs to be done to determine if RNAi can be an efficacious control method of Dectes stem borer.
Keywords: Dectes stem borer; RNAi